ANALISIS PRESTASI KERJA BERBASIS KOMPETENSI PADA PEGAWAI SEKRETARIAT DIREKTORAT JENDERAL PERCEPATAN PEMBANGUNAN DAERAH TERTINGGAL KEMENTERIAN DESA, PEMBANGUNAN DAERAH TERTINGGAL DAN TRANSMIGRASI - Syamsi Mawardi; Pusporini Palupi Jamaludin (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
The formulation of the problem in the research is whether there is an effect of work ability on employee work performance at the Secretariat of the Directorate General of Development Acceleration of Disadvantaged Areas, Ministry of Villages, Development of Disadvantaged Areas and Transmigration The research method uses a survey with a correlational quantitative approach. The sampling technique used was saturated sampling, namely the sample research technique when all members of the population were used as samples. Based on the results of the research that has been done, it can be concluded that the work ability variable has a positive, strong and significant effect on employee work performance. This can be seen from the correlation coefficient value of 0.723, while the coefficient of determination (r²) is 0.522, meaning that the variable of ability contributes 52.2% to the employee work performance variable. The result of the significance test of the ability variable on employee work performance